2010
DOI: 10.1089/scd.2009.0149
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cells by Efficient Reprogramming of Adult Bone Marrow Cells

Abstract: Reprogramming of somatic cells provides potential for the generation of specific cell types, which could be a key step in the study and treatment of human diseases. In vitro reprogramming of somatic cells into a pluripotent embryonic stem (ES) cell-like state has been reported by retroviral transduction of murine fibroblasts using four embryonic transcription factors or through cell fusion of somatic and pluripotent stem cells. Here we show that mouse adult bone marrow mononuclear cells (BM MNCs) are competent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…+ cord blood cells, bone marrow mononuclear cells (BM-MNCs), and adipose tissuederived mesenchymal stem cells (AT-MSCs), have been tested and evaluated for cell reprogramming (Takahashi and Yamanaka, 2006;Kim et al, 2009;Sun et al, 2009;Aasen and Belmonte, 2010;Kunisato et al, 2010;Takenaka et al, 2010). Compared with other cell types, AT-MSCs have been shown to be compatible with embryonic stem (ES) cell culture medium and used as feeder layers for ES cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…+ cord blood cells, bone marrow mononuclear cells (BM-MNCs), and adipose tissuederived mesenchymal stem cells (AT-MSCs), have been tested and evaluated for cell reprogramming (Takahashi and Yamanaka, 2006;Kim et al, 2009;Sun et al, 2009;Aasen and Belmonte, 2010;Kunisato et al, 2010;Takenaka et al, 2010). Compared with other cell types, AT-MSCs have been shown to be compatible with embryonic stem (ES) cell culture medium and used as feeder layers for ES cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of different cell types derived from the same inbred Various other starting somatic cell populations have been used for iPS induction in the mouse, including transgenic mouse strain also negates any possible genotype effects present when trying to draw conclusions adult stomach and liver cells (2), embryonic or newborn neural progenitor cells (9,14), pancreatic β-cells (29), from different studies. While drug selection has been used extensively to generate iPS colonies, timing of drug mature B lymphocytes (10), and bone marrow hematopoietic cells (15). An important observation from these selection has been reported to greatly influence iPS colony numbers and the level of reprogramming attained studies is that the somatic cell type chosen had a significant influence on the efficiency of iPS generation and (4, 18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, our choice of using identical starting parental cells, while having the benefit of creating a system with genetically identical cells, in addition, introduced a potential bias into our comparison. This possibility was further examined by examining the gene expression profile of BM iPSCs [38]. Indeed, there was a decrease in expression of differentiationassociated genes in BM iPSCs that are associated with the parental bone marrow cells that are not shared with fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that both cell types commonly upregulated the glycolysis pathway, although through different genes in each case. We also examined 2 other published microarray data sets generated from iPSCs that were derived either by using different cocktails of reprogramming factors [37] or different starting cells [38] to determine the global validity of our comparisons and found very similar results, suggesting that the similarity of iPSCs and OF is independent of both Myc and fibroblastic parental cells. There were some key differences, however, between iPSCs and OF.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation